Kajian Perilaku Masyarakat Pesisir yang Mengakibatkan Kerusakan Lingkungan di Pantai Mangrove Desa Tanjung Rejo Kecamatan Percut SEI Tuan - Hasiibuan, Arini Salsabila; Nasution, Aldi Syahputra; Thoibah, Baldatun; Pratiwi, Dwika Ardelya; Ayenti, Erika; Pratiwi, Khairani Putri; Br Barus, Maharani; Sirait, Salshabila Azzahra; Priyatna, Sekar Harum; Mawaddah, Qisti; Ayu, Delfriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the most common places found is the beach. The beach is where the tide meets the land. Beaches are one of the rapidly growing tourist destinations and have strategic potential, such as the mangrove beach. The most common environmental problem is waste. High waste production will definitely have an impact on the environmental health involving communities and other living creatures. The purpose of this research is to understand the behavior of the community that causes environmental damage. This research uses a quantitative descriptive method where data is collected through questionnaires with simple random sampling techniques. The results show that coastal community behavior tends to be less favorable because it causes environmental damage at the mangrove beach. The conclusion of this research is that community behavior falls into the less favorable category, causing environmental damage at the mangrove beach. This is supported by the overall results, where the activities of the population (50%), natural resource conditions (80%), and mangrove conditions (53.3%) all fall into the less favorable category.